An unsupervised semantic segmentation method that combines the ImSE-Net model with SLICm superpixel optimization - Zenan Yang; Haipeng Niu; Xiaoxuan Wang; Liang Huang; Kui Yang (International Journal of Digital Earth, 2024)
ABSTRACTIn the field of remote sensing, using a large amount of labeled image data to supervise the training of fully convolutional networks for the semantic segmentation of images is expensive. However, using a small amount of labeled data can lead to reduced network performance. This paper proposes an unsupervised semantic segmentation method that combines the ImSE-Net model with SLICm superpixel optimization. First, the ImSE-Net model is used to extract semantic features from the image to obtain rough semantic segmentation results. Then, the SLICm superpixel segmentation algorithm is used to segment the input image into superpixel images. Finally, an unsupervised semantic segmentation model (UGLS) is used to combine high-level abstract semantic features with detailed information on superpixels to obtain edge-optimized semantic segmentation results. Experimental results show that compared with other semantic segmentation algorithms, our method more effectively handles unbalanced areas, such as object boundaries, and achieves better segmentation results, with higher semantic consistency.